ANALISIS EFISIENSI BANK UMUM SYARIAH DEVISA DI INDONESIA DENGAN METODE DATA ENVELOPMENT ANALYSIS STUDI PADA BANK MUAMALAT INDONESIA DAN BANK SYARIAH MANDIRI - Haris, Helmi; Hastuti, Nuning Sri (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2013)
Performance is one of the indicators of efficiency in a firm including Islamic banks. Performance measurament commonly done by Islamic banks using financial ratio. However performance measurament by using financial ratio can’t show the condition of Islamic banks truthfully. Data Envelopment Analysis (DEA) method can overcome restrictiveness of performance measurament which able to handle many input and output. DEA method is a linier programming which aim to maximize input and output. This study aims to aware and analyze financial performance of Islamic commercial bank with DEA method in period 2008-2011. The sample of two Islamic commercial bank: Bank Muamalat Indonesia and Bank Syariah Mandiri. This study uses input variables consist of deposits, assets, and personnel costs as well as using a variable output which comprises the amount of financing and operating income. These results indicate that Islamic commercial bank foreign exchange continue to have 100 percentefficiency is a Bank Muamalat Indonesia over a period of observation, while Bank Syariah Mandiri has 100 percent efficiency in Maret 2008, September 2008, Desember 2008, Juni 2009, September 2009, Desember 2009, September 2010, Desember 2010, Maret 2011, Juni 2011, September 2011 dan Desember 2011